2020
DOI: 10.1024/0300-9831/a000662
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factors correlated with vitamin D deficiency in patients with obesity scheduled for bariatric surgery: A single center experience

Abstract: Abstract. We aim to assess the prevalence of vitamin D deficiency (VDD) in patients scheduled for bariatric surgery (BS), and to identify factors that might be associated with VDD. We conducted a cross-sectional observational study involving all consecutive patients scheduled for BS from 2017 to 2019. The exclusion criteria were missing data for vitamin D levels, intake of vitamin D supplements in the 3 months prior to serum vitamin D determination, and renal insufficiency. A total of 206 patients (mean age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Furthermore, body weight (BW) reduction is associated with improvements in OSAS, with a 10% reduction in BW predicting an approximate 26-32% change in the AHI score [9]. An accurate preoperative multidisciplinary assessment of bariatric patients plays an important role in improving performance status, surgical outcome, and WL [10][11][12][13][14][15][16][17]. Previous studies have reported that a low-calorie ketogenic diet (LCKD) is safe and effective in reducing BW and liver volume in patients scheduled for BS, resulting in a reduction of intraoperative complications and operating time [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, body weight (BW) reduction is associated with improvements in OSAS, with a 10% reduction in BW predicting an approximate 26-32% change in the AHI score [9]. An accurate preoperative multidisciplinary assessment of bariatric patients plays an important role in improving performance status, surgical outcome, and WL [10][11][12][13][14][15][16][17]. Previous studies have reported that a low-calorie ketogenic diet (LCKD) is safe and effective in reducing BW and liver volume in patients scheduled for BS, resulting in a reduction of intraoperative complications and operating time [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The highest average level was reported in those from South America which was higher than the normal range. Lower dietary intakes of calcium with decreased serum calcium levels can justify the higher levels of PTH in South American cohorts [ 176 , 177 ], which can be detrimental for bone health.…”
Section: Discussionmentioning
confidence: 99%
“…A reverse association was found between body mass index (BMI) and vitamin D level [14,15] in some studies, while the others found no association between BMI and vitamin D [16,17].…”
Section: Introductionmentioning
confidence: 99%